2019
DOI: 10.1371/journal.pone.0220711
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of high-risk SNPs in human CHK2 gene responsible for hereditary breast cancer: A functional and structural impact

Abstract: Nowadays CHK2 mutation is studied frequently in hereditary breast and ovarian cancer patients in addition to BRCA1/BRCA2. CHK2 is a tumor suppressor gene that encodes a serine/threonine kinase, also involved in pathways such as DNA repair, cell cycle regulation and apoptosis in response to DNA damage. CHK2 is a well-studied moderate penetrance gene that correlates with third high risk susceptibility gene with an increased risk for breast cancer. Hence before planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…These tools find out the possible conserved residues, mutations with the chance of most functionality, possible altered molecular mechanism, structural change in the protein, decreasing protein stability, post-translational modifications (PTM), and other predictable changes to recognize the most significant SNPs [17,18]. Now-a-days such computational research has become popular to find pathogenicity of genes, such as CSN3, RETN, FOXC2, CHK2 and so on [17][18][19][20]. Through our study, it may be possible to identify and predict new SNPs that can be associated with possible diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These tools find out the possible conserved residues, mutations with the chance of most functionality, possible altered molecular mechanism, structural change in the protein, decreasing protein stability, post-translational modifications (PTM), and other predictable changes to recognize the most significant SNPs [17,18]. Now-a-days such computational research has become popular to find pathogenicity of genes, such as CSN3, RETN, FOXC2, CHK2 and so on [17][18][19][20]. Through our study, it may be possible to identify and predict new SNPs that can be associated with possible diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The GWAS database was used to identify nsSNPs associated with cancer risks as it is the most extensive SNPs database 20 . We only focused on nsSNPs as they are capable of altering protein function, structure, conformation, and interaction which cause the increased risk of cancer 8 – 10 , 56 – 58 . Out of the 80 nsSNPs associated with cancer risks from the GWAS dataset, a total of 52 nsSNPs were identified among the Orang Asli and Malays (43 in Orang Asli and 43 in Malays).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nsSNPs cause numerous genetic disorders such as inflammatory and autoimmune disorders and cancers 8 – 10 . With the massive human genome sequence data now available and we are yet to know the functional effects of some of the SNPs, a more cost-effective approach is required to unravel the functions of the unknown SNPs effects.…”
Section: Introductionmentioning
confidence: 99%
“…• using known pathways from public databases [194,216,217], which consists of the comparison of genetic modifications related to cancer with pathways already reported in the literature through the application of statistical and machine learning methods; • network-based methods [193,195,218], identifying cancer-associated genes and pathways related with interactions at the cellular and molecular level in biological networks; • learning cancer pathways de novo [196,219], making deductions on cancer genes and pathways based on the identification of co-occurrence patterns or mutual exclusivity between genetic aberrations, without replicating state-of-the-art knowledge.…”
Section: In Silico Models In Breast Cancermentioning
confidence: 99%